Ciencias sociales 9 EGB - MEREGA, Herminia dir. (SANTILLANA, 2001)
CONTENIDO : PERES-TROIKA; CONSTITUCION NACIONAL ARGENTINA COLAB.GARCIA, P.; MINVIELEE, S.; MONTENEGRO, S.; PRIVITELLIO, L.; CATTARUZZA, A.; CARROZZA, W.; FUNES, E.; ROMANO, S.; CATTANEO, L.; HIRSCHMANN, P.; SASA, M.; DONATELLO, L.; SANTILLANA